A cidade de notícias: um estudo do jornalismo de influência regional de Imperatriz no Maranhão - Reis, Thays Assunção (Universidade do Estado do Rio de Janeiro, 2022)
This thesis investigates the media services and the role of journalism in the medium city of Imperatriz (MA) within its region of influence. The question that guides this research is: how are media services configured in medium-sized cities and what is the function of the journalism produced by them in the regional context? Based on this question, the general objective of the thesis is to investigate the media services of the medium city of Imperatriz (MA) and the role of its journalism in the regional context. Its specific objectives are: 1) to map and characterize the media services, flows and journalistic newsrooms in Imperatriz; 2) to analyze the news produced and distributed by the press vehicles of Imperatriz; 3) to know the perception of Imperatriz journalists on the news they produce and the routines of regional coverage; 4) identify the existing media services in the small towns of the region of Imperatriz and verify the presence of local information production there; and 5) understand how the consumption of news by local residents and the surroundings of Imperatriz occurs. To achieve the proposed objectives, we adopted the methodological triangulation strategy combining the following procedures: a) mapping of the communication vehicles in operation in the investigated cities; b) semi-structured interviews with journalists from Imperatriz; c) survey with residents of Imperatriz and cities in its region of influence; and d) content analysis of journalistic products. At the end of the study, we identified the strong media centrality of Imperatriz expressed by the presence of 18 media services, among which those of the highest order in the production of news and information, in this case, open TV stations, daily newspapers and radio FM stations. These media form a network of information flows distributed among cities in Maranhão, Tocantins and Pará. Small cities in the region present low-order media initiatives, with simpler infrastructures technologically, of low cost and with flows restricted to their territories. Such places present limited production of local information and permeated by political interests. They are, therefore, considered news deserts. It is evident in Imperatriz a journalistic activity specialized in: a) simultaneous production of local and regional news, which we call 'polarizing news'; b) carrying out news coverage of the region of influence; c) mediation of the demands and claims of the small surrounding communities; d) proximity information for consumption in the region; e) intermediation of information flows produced in other urban centers. Together, these characteristics give shape to a journalism with a differentiated performance potential in the context outside the metropolitan regions, which we call Journalism of Regional Influence.